Médecine et sexualité, aperçus sur une rencontre historiographique (Recherches francophones, époques moderne et contemporaine) - Chaperon, Sylvie; Hanafi, Nahema (Clio. Femmes, Genre, Histoire, 2013)
Cet article rappelle dans quelles circonstances une histoire de la sexualité construite à partir de sources médicales a émergé en France dans les années 1970. Il insiste surtout sur les pionnier-e-s de cette histoire pour les périodes moderne et contemporaine et les sources qu’ils et elles ont utilisées. Enfin il met en avant le renouvellement récent de ce champ grâce à une histoire « par en bas ».
ISBN: 9782701177816 Number: 37 Publisher: Éditions Belin
Keywords: 1900-1999; 1970-1979; 1980-1989; approches et analyses; corps; cours; discipline; discours dominant; europe; france; histoire et politique; justice sociale; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; violences

Orchids, intersex and the auto/biographical project - Hart, Phoebe (Studies in Documentary Film, 2013)
Auto/biographical documentaries ask audiences to take a ‘leap of faith’, not being able to offer any real 'proof of the people and events they claim to document, other than that of the film-maker's saying this is what happened. With only memory and history seen through the distorting lens of time, ‘the authenticity of experience functions as a receding horizon of truth in which memory and testimony are articulated as modes of salvage’. Orchids: My Intersex Adventure follows a salvaging of the film-maker's life events and experiences, being born with an intersex condition, and, via the filming and editing process, revolving around the core question: who am I? From this transformative creative documentary practice evolves a new way of embodying experience and ‘seeing’, playfully dubbed here as the ‘intersex gaze’.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; australie; autoethnographie; cinéma; cinéma documentaire; communication; corps; cours; discipline; discours dominant; identités; intersexuation; inégalités; océanie; premier cycle; périodes historiques; régions géographiques; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales